Dynamics of Magnetically Trapped Particles Foundations of the Physics of Radiation Belts and Space Plasmas - Roederer, Juan G.; Zhang, Hui.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book is a new edition of Roederer$1 (Bs classic Dynamics of Geomagnetically Trapped Radiation, updated and considerably expanded. The main objective is to describe the dynamic properties of magnetically trapped particles in planetary radiation belts and plasmas and explain the physical processes involved from the theoretical point of view. The approach is to examine in detail the orbital and adiabatic motion of individual particles in typical configurations of magnetic and electric fields in the magnetosphere and, from there, derive basic features of the particles$1 (Bcollective (3z(Bmacroscopic(3y (Bbehavior in general planetary environments. Emphasis is not on the (3z(Bwhat(3y (Bbut on the (3z(Bwhy(3y (Bof particle phenomena in near-earth space, providing a solid and clear understanding of the principal basic physical mechanisms and dynamic processes involved. The book will also serve as an introduction to general space plasma physics, with abundant basic examples to illustrate and explain the physical origin of different types of plasma current systems and their self-organizing character via the magnetic field. The ultimate aim is to help both graduate students and interested scientists to successfully face the theoretical and experimental challenges lying ahead in space physics in view of recent and upcoming satellite missions and an expected wealth of data on radiation belts and plasmas.s
Particle Drifts and the First Adiabatic Invariant -- Particle Trapping, Drift Shells and the Second Adiabatic Invariant -- Periodic Drift Motion and the Third Adiabatic Invariant -- Trapped Particle Distributions and Flux Mapping -- Violation of the Adiabatic Invariants and Trapped Particle Diffusion -- Introduction to Plasma Physics.
Keywords: Physics; Physical geography; Astrophysics; Magnetism; Physics; Extraterrestrial Physics, Space Sciences; Plasma Physics; Geophysics/Geodesy.; Applied and Technical Physics; Magnetism, Magnetic Materials